Evaluation of Communication Skills Among Physicians: A Systematic Review of Existing Assessment Tools. Issue 4 (May 2020) - Boucher, Vincent Gosselin; Gemme, Claudia; Dragomir, Anda I.; Bacon, Simon L.; Larue, Florent; Lavoie, Kim L.
ABSTRACT: Objective: The importance of physician training in communication skills for motivating patients to adopt a healthy life-style and optimize clinical outcomes is increasingly recognized. This study inventoried and systematically reviewed the psychometric properties of, and the skills assessed by, existing assessment tools used to evaluate communication skills among physicians. Methods: This review was conducted in accordance with the PRISMA guidelines (PROSPERO: CRD42018091932). Four databases (PUBMED, EMBASE, PsychINFO, and SCOPUS) were searched up to December 2018, generating 3902 unique articles, which were screened by two authors. A total of 57 articles met the inclusion criteria and underwent full data extraction. Results: Forty-five different assessment tools were identified. Only 47% of the studies mentioned underlying theories or models for designing the tool. Fifteen communication skills were assessed across the tools, the five most prevalent were information giving (46%) or gathering (40%), eliciting patients' perspectives (44%), planning/goal setting (37%), and closing the session (32%). Most tools (93%) assessed communication skills using in-person role play exercises with standardized (61%) or real (32%) patients, but only 54% described the expertise of the raters who performed the evaluations. Overall, reporting of the psychometric properties of the assessment tools was poor-moderate (4.5 ± 1.3 out of 9). Conclusions: Despite identifying several existing physician communication assessment tools, a high degree of heterogeneity between these tools, in terms of skills assessed and study quality, was observed, and most have been poorly validated. Research is needed to rigorously develop and validate accessible, convenient, "user-friendly, " and easy to administer and score communication assessment tools. Abstract : Supplemental digital content is available in the text.